Street market saleswomen: strategies for the recognition of health needs - Ana Hirley Rodrigues Magalhães; Maria Adelane Monteiro da Silva; José Reginaldo Feijão Parente; Ivna de Holanda Pereira; Maristela Inês Osawa Vasconcelos; Leidy Dayane Paiva de Abreu; Vytal Hirvey Magalhães Arruda Linhares (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to describe the strategies used by street market saleswomen to recognize their health needs. Methods: qualitative research, based on the Human Needs Theory. The data were collected through semi-structured interviews, with the participation of 15 street market saleswomen. Content Analysis was used to interpret the results. Results: the following categories emerged: "Potentialities and challenges for addressing health needs", which reflect changes in attitudes and practices related to socially recognized behaviors as harmful, and changes in the work process; and "Popular practices in health care", which points out therapeutic alternatives for the resolution of health problems. Final considerations: the therapeutic choices of street market saleswomen are geared towards meeting their perceived health needs. While the minority of these women recognize their more complex health needs to satisfy it, it is necessary to overcome barriers and limitations in an ongoing way in their lives.